HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG STATUS GIZI DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI PUSKESMAS SIMPANG TIGA KECAMATAN BUKIT KABUPATEN BENER MERIAH - Imanna, Nur; Hudnah; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Maternal nutritional status plays an important role in the continuity and success of a pregnancy. Disturbances in nutritional intake during pregnancy cause chronic diseases, namely Chronic Energy Deficiency (CED). Data from the World Health Organization (WHO) shows that the prevalence of CED in pregnant women in the world reaches 41%. The aim of this research is to determine the relationship between knowledge and attitudes about nutritional status and the incidence of chronic energy deficiency (KEK) in pregnant women at the Simpang Tiga Community Health Center, Bukit District, Bener Meriah Regency. The type of research used is quantitative with a cross sectional study approach. The population in this study were all pregnant women who came to the Simpang Tiga Health Center, Bukit District, Bener Meriah Regency, 31 pregnant women, the total sample was 31 people using the total sampling method. The analysis used is the Chi-square test. The results show that there is a relationship between nutritional knowledge and the incidence of chronic energy deficiency in pregnant women (p=0.019), there is a relationship between nutritional attitudes and the incidence of chronic energy deficiency in pregnant women (p=0.005). Conclusion: Pregnant women can increase their antenatal care visits to reducing the incidence of chronic energy deficiency in pregnant women. Keywords : Knowledge, Attitude, KEK